Dalla realtà alla poesia. Lettere di Filippo de Pisis a Giuseppe Marchiori - Lucia Bonazzi (Annali Online dell'Università di Ferrara. Sezione Lettere, 2022)
The Archive “Giuseppe Marchiori” which is kept in the Municipal Library in Lendinara, preserves the letters the painter Filippo de Pisis wrote to the art critic Giuseppe Marchiori. They met in 1926 during the XVII exhibition of Cà Pesaro in Lido of Venice thanks to the painter Juti Ravenna. An exchange of news, care and projects, fully transcribed for the first time, which gives back cultural unrest that began with the publication of Giovanni Cavicchioli’s monograph on de Pisis, for Marchiori’s North-East Editions (1932). Both collaborated with the Bolognese magazine «L’Orto», for which de Pisis, member of the Italiens de Paris group, created articles and illustrations. Marchiori published many reviews on de Pisis' work, for example in «Emporium» (1936) and in «Corriere Padano» (1938), considering it a privileged channel in order to connect to the new artistic movements in Paris.